The shaping of aquatics education in New Zealand schools : an historical study of curriculum policy and practice : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Education at Massey University - Moran, Kevin (Massey University, 1999)
The teaching of aquatic activities has traditionally held a prominent position in the curriculum of New Zealand schools. In particular, the promotion of swimming and water safety skills and knowledge have long been valued as a community good. Given the geographical disposition of an island nation with its extensive coastline, fast-flowing rivers and large tracts of inland water, as well as the propensity of its citizens to associate with water-related activities both at work and play, such promotion seems entirely justified. In the context of today's society, the aquatic environment has been identified as the second most important location for public leisure and recreation with over half of New Zealand's population identifying water-related activity as being significant in their lifestyle (LINZ Survey, 1991) However, even though the prophylactic and pragmatic values of aquatic competency were recognized at an early date, little is known about what historical influences have helped shape current practice in the promotion of such values, nor indeed to what extent aquatics education has been reflective of, or reactive to, changes in societal values, attitudes and practices throughout its development This thesis examines the historical development of aquatics education using historical research In particular, the historical research concentrates upon the relationship between aquatics education and the social context in which its development has taken place. Such a concentration is considered particularly relevant in a study of aquatics education because of the high public profile that swimming and water safety have had throughout New Zealand's brief history - a profile that is best reflected in the frequently expressed public and private concerns regarding the high levels of death by drowning as well as the high incidence of water-related rescues. Finally, rather than view the development of aquatics education as part of a progressive, liberal educational enterprise so often reflected in official documents, this study presents evidence supporting the view that aquatics education, as part of curriculum practice, is a site of contestation that is socially constructed and which presents itself as a discursive legacy reflecting the dynamic interaction of numerous socio-cultural forces operating at an instance in time.
Keywords: New Zealand -- History; Study and teaching; Swimming; Diving; Aquatic sports